2009
DOI: 10.1080/09540120802511984
|View full text |Cite
|
Sign up to set email alerts
|

Disassortative sexual mixing among migrant populations in the Netherlands: a potential for HIV/STI transmission?

Abstract: To gain insight into the transmission of HIV and sexually transmitted infection (STI) among large migrant groups in The Netherlands, we studied the associations between their demographic and sexual characteristics, in particular condom use, and their sexual mixing patterns with other ethnic groups. In 2002-2005, cross-sectional surveys were conducted among migrants from Surinam (Afro- and Hindo-), the Netherlands Antilles, Cape Verde, and Ghana at social venues in three large cities. A questionnaire was admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 22 publications
3
16
0
1
Order By: Relevance
“…SD: +++ V: +++ G: ++ OS: +++Data does not support some of the conclusions. Authors do not acknowledge limitations of surveillance data.van Veen et al (2009) [27] Sexual mixing: Partners from the same ethnicity 59 %, Partners with differing ethnicity 41 % (15 % with Dutch partners; 21 % with partners of “Other” ethnicity; 5 % with both Dutch and “Other”).SD: +++ V: +++ G: ++ OS: +++Desirability bias ; convenience sample; auto-selection bias.BA = Black African, BC = Black Caribbean, SSA = Sub Saharan African, SEP = Socioeconomic Position, MSM = Men who have sex with men SD = Study Design, V = Validity, G = Generalisability, OS = Overall Score, N/A = Not applicable…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SD: +++ V: +++ G: ++ OS: +++Data does not support some of the conclusions. Authors do not acknowledge limitations of surveillance data.van Veen et al (2009) [27] Sexual mixing: Partners from the same ethnicity 59 %, Partners with differing ethnicity 41 % (15 % with Dutch partners; 21 % with partners of “Other” ethnicity; 5 % with both Dutch and “Other”).SD: +++ V: +++ G: ++ OS: +++Desirability bias ; convenience sample; auto-selection bias.BA = Black African, BC = Black Caribbean, SSA = Sub Saharan African, SEP = Socioeconomic Position, MSM = Men who have sex with men SD = Study Design, V = Validity, G = Generalisability, OS = Overall Score, N/A = Not applicable…”
Section: Resultsmentioning
confidence: 99%
“…Elford et al (2007) [26] state that 80 % of black African heterosexuals reported sexual partners of the same ethnicity and van Veen et al (2009) [27] found that 41 % of their sample had partners with different ethnicity (15 % with Dutch partners). Similarly Marisciano et al (2013) reported that 50 % of men and 47 % of women had partners from a different country although most were from another African country [28].…”
Section: Resultsmentioning
confidence: 99%
“…Studies on sexual networks among migrants tend to have focused on sexual contact between migrants from countries with generalised HIV epidemics and native populations (Gras et al 1999(Gras et al , 2001Van Veen et al 2009;Wiggers et al 2003;Xiridou et al 2010) -the crucial question here being the potential epidemic spread from these groups to the so-called general population, with little attention being paid to sexual mixing between migrants from different sub-Saharan African countries. Our analyses provide evidence of the existence of African sexual networks, over and beyond national origin.…”
Section: Migrants From Over There and Racial Minorities Herementioning
confidence: 99%
“…An over-representation of young, highly educated and recently arrived migrants While for reasons of feasibility, surveys among migrants tend to favour convenience sampling (Gras et al 1999;Sadler et al 2006;Van Veen et al 2009), this survey has relied on random recruitment (Lydié 2007;Lydié, Guilbert, and Sliman 2008). However, due to the overall low response rate, the sample may seem closer to a convenience sample.…”
Section: Random Recruitment With Gender-and Ethnically-matched Intervmentioning
confidence: 99%
See 1 more Smart Citation